Drosophila as a Promising In Vivo Research Model for the Application and Development of Targeted Protein Inactivation Technologies. - Dorogova, N.V.; Fedorova, S.A. (Archives of Insect Biochemistry and Physiology, 2025)
Technologies for controlled protein targeting allow the selective manipulations of proteins resulting in their degradation and/or loss of function. Over the past two decades, these technologies have overcome the limitations of genetic methods and have become powerful tools in biological research and the search for new therapeutic approaches to disease treatment. Various methods of protein degradation and inactivation have been successfully applied to a model organism such as Drosophila melanogaster. In this article, we overview the capabilities and prospects of the Drosophila in vivo model for testing and developing modern methods of controlled protein targeting, analyzing their efficacy at the organism level and solving fundamental biological problems.